Overview of The Level of Knowledge of Adolescent Girls About The Habit of Wearing Underwear in Relation to Reproductive Health at Muhajirin Cikupa Junior High School - Ismy Nur Isnaini; Fischa Awalin; Sudrajat (Nusantara Sehat: Jurnal Kesehatan Indonesia, 2025)
Young women are an age group that undergoes physical changes and reproductive organ maturation. One of the important aspects of maintaining reproductive health is the habit of wearing underwear. The use of underwear that is too tight, does not absorb sweat, or is rarely changed can increase the risk of vaginal discharge, irritation, and infection. However, there are still many teenagers who have limited understanding of this matter. Objective: This study aims to find out the level of knowledge of adolescent girls regarding the habit of using underwear in reproductive health at Muhajirin Cikupa Junior High School. This study used quantitative with a descriptive design. The sample was taken by random sampling of 104 adolescent girls aged 12–15 years at Muhajirin Cikupa Junior High School. The instrument was in the form of a closed questionnaire with 21 statements that included the hygiene of the reproductive organs, the selection and use of underwear, the habit of changing underwear, and the impact of improper use. The data were analyzed univariately and presented in frequency distributions. Most of the respondents were 13 years old (39.4%) and in grade VII (35.6%). As many as 85.6% of respondents had a good level of knowledge, 14.4% were adequate, and nothing was lacking. High knowledge can be seen in the hygiene aspect of the reproductive organs and the habit of changing underwear, although there are still misunderstandings related to the use of cleaning soaps containing alcohol and fragrances for the reproductive organs. Conclusion: The majority of young women have good knowledge, but further education is still needed so that this knowledge can be applied consistently in their daily habits. Keywords: Knowledge, Young Women, Underwear, Reproductive Health